Deliberative Public Engagement with Science: An Empirical Investigation - PytlikZillig, Lisa M.; Hutchens, Myiah J.; Muhlberger, Peter; Gonzalez, Frank J.; Tomkins, Alan J. (Springer Nature, 2021)
experimental manipulations of deliberative engagement; nanotechnology public policy issues; education-oriented communications; experimental social science; science, technology and society; innovation policy; cognitive-affective engagement; polarization of public attitudes